The Effect Of Young Coconut Water Mouth (Cocus Nucifera L) Against Dental Plaque - Habibah, Siti Sab'atul; Danan, Danan; Ulfah, Rasuna (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2023)
Caries is a disease of the hard tissue of the teeth caused by bacteria adhering to the surface of the teeth in the form of plaque. The formation of dental plaque can be prevented by plaque control including mechanical control and chemical control, one of which is gargling using natural ingredients, namely young coconut water (Cocus Nucifera L Var. Viridis). Pure coconut water has antimicrobial activity due to its high lauric acid content and has been used as a remedy for several oral infections. This study aims to determine the effect of young coconut water gargling (Cocus Nucifera L Var. Viridis) on dental plaque. The type of research used was quasi-experimental with a pretest and posttest one group design. The sample in this study was taken by means of purposive sampling totaling 44 people. Measurements were made before and after consuming 100 ml of young coconut water (Cocus Nucifera L Var. Viridis). Plaque was measured using the Personal Hygiene Performance (PHP) method. Data analysis used the Mann-Whitney test. The results of the study gargling young coconut water (Cocos Nucifera L Var. Viridis) 1.31 and after decreasing 0.47. There was a significant difference between before and after gargling young coconut water (Cocos Nucifera L Var. Viridis) p=0.000. The conclusion in this study was that gargling with young coconut water (Cocos Nucifera L Var. Viridis) had an effect on reducing the dental plaque index